2014
DOI: 10.1007/s12291-014-0447-z
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of Insulin Resistance and Serum Testosterone Levels with LH:FSH Ratio and Oxidative Stress in Women with Functional Ovarian Hyperandrogenism

Abstract: Functional ovarian hyperandrogenism (FOH) is a form of polycystic ovary syndrome (PCOS) characterized by elevated circulating levels of androgens derived from the ovary. Insulin resistance (IR) is the most common etiological factor in women with FOH. IR causes the generation of increased oxidative stress (OS) and diminished antioxidant status. OS is directly correlated with both IR and testosterone levels, which consequently contribute to endocrine and biochemical alterations in FOH women. In the current study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 28 publications
3
19
0
Order By: Relevance
“…Suresh et al . recently reported a correlation of both insulin resistance and testosterone levels with oxidative stress in women with functional hyperandrogenism . According to the results of our study, hyperandrogenism in itself, although increased in the PCOS group, does not play a significant role in the increased CVD risk in overweight adolescents with PCOS.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Suresh et al . recently reported a correlation of both insulin resistance and testosterone levels with oxidative stress in women with functional hyperandrogenism . According to the results of our study, hyperandrogenism in itself, although increased in the PCOS group, does not play a significant role in the increased CVD risk in overweight adolescents with PCOS.…”
Section: Discussionsupporting
confidence: 64%
“…Suresh et al recently reported a correlation of both insulin resistance and testosterone levels with oxidative stress in women with functional hyperandrogenism. 42 According to the results of our study, hyperandrogenism in itself, although increased in the PCOS group, does not play a significant role in the increased CVD risk in overweight adolescents with PCOS. Thus, we conclude that increased androgen levels may have an influence on oxidative stress, but not alone, rather with the additive effects of other factors such as insulin resistance and overweight status.…”
Section: Discussionmentioning
confidence: 47%
“…Previous studies have demonstrated that a positive association between hyperandrogenism, hyperinsulinemia, and insulin resistance in females with elevated androgen levels due to PCOS [45,46]. In addition, oxidative stress is directly correlated with both insulin resistance and hyperandrogenism, which in turn contribute to endocrine and biochemical alterations in women with functional ovarian hyperandrogenism (FOH) [47]. The present study revealed that taking selenium supplements in PCOS patients for 8 weeks was associated with decreased serum hs-CRP levels, but did not affect plasma NO concentrations.…”
mentioning
confidence: 99%
“…Increased oxidative stress was found to correlate directly with IR as well as serum testosterone and androstenedione levels (30). IR appears to activate the critical enzyme responsible for the synthesis of androgens, cytochrome p450-c17α-hydroxylase, in ovarian theca cells (Fig.…”
Section: Hyperandrogenism and Ir In Pcosmentioning
confidence: 99%